New challenges for the water supply sector in view of the new Drinking Water Directive – The Investment Program as a multifaceted instrument of legal, substantive and financial support - Zimoch, Izabela; Mulik, Barbara; Bogucka-Szymalska, Małgorzata; Szymura, Ewa; Łyskawka, Sylwia (Instal, 2020)
The aim of the December plenary session of the European Parliament will be to adopt the final version of the new Drinking Water Directive (DWD). This version of DWD is an effect of negotiations lasting for nearly 3 years with the Council of the Union and the European Commission. According to the EU legislative procedures, Member States must implement this new directive into national law within two years from the date of its publication in the Official Journal of EU. This article presents the significance the water supply sector needs to be assessed in terms of both the actual level of implementation of Directive 98/83/EC and achieving its goal in Poland. Moreover, the assumptions of the developed methodology for assessing the readiness of all entities to implement the provisions of the new Directive 2017/0332 (COD) were presented by all interested parties. Furthermore, this paper depicted the importance of a questionnaire survey for formulation of reliable assumptions into the Investment Plan for the New EU Financial Perspective 2021-2027.